2018
DOI: 10.1186/s12871-018-0477-9
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative incidence of airway obstructive and hypoxemic events in patients with confirmed or suspected sleep apnea - a prospective, randomized pilot study comparing propofol/remifentanil and sevoflurane/remifentanil anesthesia

Abstract: BackgroundObstructive sleep apnea (OSA) is a risk factor for perioperative complications but data on anesthesia regimen are scarce.MethodsIn patients with established or strongly suspected OSA, we assessed in a prospective, randomized design the effects on nocturnal apnea-hypopnea-index (AHI) and oxygen saturation (SpO2) of propofol/remifentanil or sevoflurane/remifentanil based anesthesia. Patients were selected by a history for OSA and / or a positive STOP – questionnaire and received general anesthesia usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“… 154 , 155 However, sevoflurane was found to be superior to propofol in 2 RCTs due to faster anesthesia recovery and improved hemodynamic stability. 152 , 153 In addition, recently Fassbender et al 151 reported no difference with regard to postoperative obstructive and hypoxemic events between the 2 anesthetic agents when combined with remifentanil. Furthermore, comparing propofol and desflurane, 1 study demonstrated that the use of propofol impaired pulmonary function and SpO 2 to a greater degree than desflurane, 157 while another could not confirm these differences.…”
Section: Intraoperative Medication Use In Patients With Osamentioning
confidence: 99%
See 2 more Smart Citations
“… 154 , 155 However, sevoflurane was found to be superior to propofol in 2 RCTs due to faster anesthesia recovery and improved hemodynamic stability. 152 , 153 In addition, recently Fassbender et al 151 reported no difference with regard to postoperative obstructive and hypoxemic events between the 2 anesthetic agents when combined with remifentanil. Furthermore, comparing propofol and desflurane, 1 study demonstrated that the use of propofol impaired pulmonary function and SpO 2 to a greater degree than desflurane, 157 while another could not confirm these differences.…”
Section: Intraoperative Medication Use In Patients With Osamentioning
confidence: 99%
“…In this context, 25 studies were identified that compared the efficacy and recovery profile among the most common inhalational agents and intravenous propofol. 65 , 151 174 A summary of evidence is provided in Supplemental Digital Content, Tables A7 and A8, http://links.lww.com/AA/C373 . Comparing propofol and isoflurane, propofol was suggested to be associated with a faster recovery from anesthesia and improved postoperative respiratory control in 2 RCTs.…”
Section: Intraoperative Medication Use In Patients With Osamentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 The prevalence of OSAS in the general population, around 11.4% for men and 4.7% for women and is expected to increase every year. 6 OSAS screening can be done using the Berlin questionnaire and the Epworth Sleepness Scale (ESS) questionnaire. 7 But, the gold standard for diagnosis of OSAS can definitely use polysomnography (PSG).…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Apart from all clinical and scientific advances regarding OSAS, most (70-90%) people affected by OSAS remain undiagnosed. 6 Lack of patient awareness, medical personnel have not received the training needed to help speed up case finding, and the high price of PSG examinations as gold OSAS standards are the cause of many undiagnosed OSAS patients. Therefore, knowledge of risk factors for OSAS is important to direct diagnostic attention to those with the highest risk.…”
Section: Introductionmentioning
confidence: 99%